حكم عقـــد الزواج عبر وسائل الاتصـــال الحديثـــة - دشاش, راضية (مجلة مالك بن نبي للبحوث والدراسات, 2021)
يشهد العالم ثورة رقمية في جميع مجالات الحياة وحركة كبيرة في مجال المعلوماتية ، واستخدام تكنولوجيا الاتصال الحديثة لقدرتها الهائلة في تسهيل عملية نقل وإرسال المعلومات. حيث أصبح التعامل بهذه المخترعات في إبرام العقود المالية والتجارية وحتى الشخصية كعقد الزواج عبر وسائل الاتصال الحديثة الأمر الذي يتطلب نوعا من الحماية والثبات ذلك أن الكثير من الشباب قد يقعون ضحية نصب واحتيال جراء هذا الزواج الأمر الذي يدفع إلى التساؤل عن حكم الزواج عبر وسائل الاتصال الحديثة ؟ وفي حالة حصل ذلك ماهي أهم الوسائل التي يمكن للأطراف الاعتماد عليها لإثبات الزواج عبر وسائل الاتصال ؟ خاصة أنها مسألة مستجدة أصبحت تأثر على الأمن الأسري والاجتماعي وعليه فالقول بجواز الزواج عبر التقنيات المعاصرة لا يعني التوسع فيه وإنما يبقى اللجوء إليه في حالة ظروف لا تسمح للأفراد باللقاء، ومن ثمة تنبيه المشرع الجزائري لهذا الوضع الحساس من خلال النص على عقد الزواج عبر وسائل الاتصال الحديثة في قانون الأسرة وبيان طرق خاصة لإثباته تختلف عن غيرها . The world is witnessing a digital revolution in all areas of life as well as a great movement in the field of informatics, including the use of modern communication technology for its enormous ability to facilitate the process of transmitting and sending information. Dealing with these inventions leads to concluding financial, commercial and even personal contracts, such as the marriage contract through modern means of communication, which requires a kind of protection and stability. As a result, many young people may fall victim to deception, and this make marriage through modern means of communication in question. And if this happens, what are the most important means that the parties can rely on to prove the marriage through modern means of communication? Especially since it is an emerging issue that has affected family and social security, and accordingly, saying that marriage is permissible through contemporary technologies does not mean expanding it, but it remains to resort to it in the case of circumstances that do not allow individuals to meet. Hence, the Algerian legislator alerts this sensitive situation by stipulating the marriage contract through modern means of communication in Family law, showing special different ways to prove it.
Keywords: Communications modernes; Contract; Contrat de mariage; Contrats; Judgment; Jugement; Marriage contract; Modern means of communication; Reporter and electronic signature; Éditeur et signature électroniques; التعاقد; الحكم; المحرر والتوقيع الالكتروني; عقد الزواج; وسائل الاتصال الحديثة